Development of simplified design techniques for estimating undrained bearing loads of piled-raft in soft clay - Tan, Kim Leong (2015)
Many structures founded on pile-raft foundations on soft clay in Singapore has been conservatively designed without considering the contribution from the raft due to the lack of knowledge (and thus design confidence) on the soil-structure interaction, bearing capacity of foundation against settlement. This generally resulted in very expensive foundation costs particularly in the soft clay conditions.